BIMBINGAN TEKNIS PEMBUATAN PUPUK KOMPOS PADA MASYARAKATPERI-URBAN DI DESA ABEKO KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - Aku, Achmad Selamet; Wahyuni, Sri; Afa, Laode; Nalefo, La; Baka, Wa Kuasa; Tamrin, Tamrin; Iba, Wa; Ruslan, Ruslan; Idaman, Idaman (MAJU : Indonesian Journal of Community Empowerment, 2024)
Thematic KKN activities carried out in Abeko Village, Ranomeeto Barat District, South Konawe Regency, focused on technical guidance on making compost for peri-urban communities. This program aims to improve community skills and knowledge in processing organic waste into environmentally friendly and economical compost. This activity is in line with efforts to support government programs in realizing sustainable agriculture and reducing dependence on chemical fertilizers that can damage the soil in the long term. The evaluation results showed that this training was able to improve the understanding and skills of participants, as evidenced by their success in making compost piles that met standards. In addition, participants were also able to identify organic materials available in the surrounding environment, such as plant residues and livestock manure, and understand how to maintain temperature and humidity during the fermentation process.